MANAJEMEN RESIKO PADA IMPLEMENTASI SAAS (SOFTWARE AS A SERVICE) - Toni Kusnandar (STMIK Mardira Indonesia, Bandung, 2015)
In recent years, Cloud Computing has evolved into a promising business concept as one of the segments of the industry's fastest growing of information technology. Many companies are increasingly aware that by leveraging the Cloud, they can gain quick access to the best business applications or drastically improve their infrastructure resources, with almost no additional cost. But as more and more individuals and corporate information stored in the Cloud, concerns began to grow about how safe the Cloud. Risk management to use SaaS selection decisions necessary so an organization can get the most of the advantages of cloud computing technologies. Risk analysis helps reduce uncertainty in decision making rational, and as long as there is uncertainty in decision making, risk evaluation will be an important component of the decision-making process. Reducing uncertainty can only be done by achieving and process more information on the initiative of the decision domain of risk analysis. Keywords: Cloud Computing, Software as a Service.